Assessing the Impact of Mesh Density on Safety Factor in 2D and 3D Finite Element Modeling: A Case Study of Landslide Mitigation with Corrugated Concrete Sheet Pile (CCSP) - Rahmawati Cupasindy, Dyah Ayu; Sholeh, Moch.; Asema, Fuji; Anggraini, Novita; Susilo, Helik; Aditya, Muhammad Tri (Westscience Press, 2025)
The problem of landslides in irrigation canal embankments often occurs in areas with soft and expansive soils that have low bearing capacity and are easily changed in volume due to fluctuations in water content. One of the main triggers is the rapid drawdown phenomenon that causes a sudden decrease in slope stability. In this study, slope stability analysis was conducted using the finite element method with PLAXIS 2D and PLAXIS 3D software. The main objective of the study was to evaluate the effect of mesh variation and soil model selection between Mohr-Coulomb Undrained A and Hardening Soil on Safety Factor (SF) value and slope settlement pattern. The reinforcement treatment analyzed was the use of Corrugated Concrete Sheet Pile (CCSP) installed on the side of the slope to improve stability. The results showed that the mesh variation affected the SF results and stress distribution patterns, especially in the 3D model. The Hardening Soil model produced more realistic deformation and SF predictions than the Mohr-Coulomb model. Thus, choosing the right soil model and mesh configuration is very influential in producing accurate analysis and can be used as a reference in the design of irrigation canal slope treatment.